Copeptin, a novel prognostic biomarker in ventilator-associated pneumonia - Seligman, Renato (2008)
Background The present study sought to investigate the correlation of copeptin with the severity of septic status in patients with ventilator-associated pneumonia (VAP), and to analyze the usefulness of copeptin as a predictor of mortality in VAP. Methods The prospective observational cohort study was conducted in a teaching hospital. The subjects were 71 patients consecutively admitted to the intensive care unit from October 2003 to August 2005 who developed VAP. Copeptin levels were determined on day 0 and day 4 of VAP. Patients were followed for 28 days after the diagnosis, when they were considered survivors. Patients who died before day 28 were classified as nonsurvivors. There were no interventions. Results Copeptin levels increased from sepsis to severe sepsis and septic shock both on day 0 and day 4 (P = 0.001 and P = 0.009, respectively). Variables included in the univariable logistic regression analysis for mortality were age, gender, Acute Physiology and Chronic Health Evaluation II score and ln copeptin on day 0 and day 4. Mortality was directly related to ln copeptin levels on day 0 and day 4, with odds ratios of 2.32 (95% confidence interval, 1.25 to 4.29) and 2.31 (95% confidence interval, 1.25 to 4.25), respectively. In a multivariable logistic regression model for mortality, only ln copeptin on day 0 with odds ratio 1.97 (95% confidence interval, 1.06 to 3.69) and ln copeptin on day 4 with odds ratio 2.39 (95% confidence interval, 1.24 to 4.62) remained significant. Conclusion Our data demonstrate that copeptin levels increase progressively with the severity of sepsis and are independent predictors of mortality in VAP.